Surgical antibiotic prophylaxis in a teaching hospital in western Nepal - Shankar, PR; Subish, P; Dubey, AK; Mishra, P; Upadhyay, DK (Journal of Institute of Medicine Nepal, 2007)
Background: Inappropriate prophylaxis favours the emergence of resistant organisms. In a previous study many parameters were not explored. Hence the present study was carried out to obtain information on the common antibiotics used for surgical prophylaxis, assess the appropriateness of antibiotic use for different procedures, calculate the mean cost of antibiotics used for prophylaxis. The prospective study was carried out over a four-month period (01.04.2004 to 31.07.2004) Manipal Teaching Hospital, Pokhara, Western Nepal. Materials and Methods: Inpatients undergoing surgery in the departments of General Surgery, Obstetrics and Gynaecology, Otorhinolaryngology and Orthopaedics. The surgeries were classified as clean, clean-contaminated, contaminated and dirty. Appropriateness of prophylaxis was assessed. The percentage of patients receiving inappropriate prophylaxis was calculated. Results: Antibiotics were used in 367 of the 371 patients who underwent surgeries. 241 surgeries (65%) were clean-contaminated, 65 (17.5%) were clean while 48 (12.9%) were contaminated. Internal fixations of fractures, circumcision, tympanoplasty, appendicectomy were common surgeries performed. Antibiotics were used for prophylaxis in 322 patients (86.8%) and for treatment in others. The fixed-dose combination of ampicillin and cloxacillin, metronidazole, gentamicin, ampicillin and cefotaxime were most commonly prescribed. The use of antibiotics was according to guidelines in 68 of the 322 patients (21.1%). The mean cost of antibiotics for prophylaxis was 11.2 US$. If a standard guideline had been followed the cost would have been reduced to 1.6 US$. Conclusions: Problems were noted in the use of antibiotics for surgical prophylaxis. Framing of antibiotic use guidelines are required. Key words: Antibiotics, Guidelines, Surgical antibiotic prophylaxis The full text of this paper is available at Journal of Institute of Medicine website